Prominent osteolysis in the maxilla: case report of an odontogenic fibroma mimicking a cyst - Clemens Raabe; Matthias Dettmer; Daniel Baumhoer; Valerie G. A. Suter (BMC, 2023)
Abstract Background Odontogenic fibroma (OF) is a rare benign odontogenic tumor of ectomesenchymal origin, mostly affecting the tooth-bearing portions of the jaws in middle-aged patients. Whilst small lesions tend to be clinically asymptomatic, varying unspecific clinical symptoms occur with an increase in size and may mimic odontogenic or other maxillofacial bone tumors, cysts, or fibro-osseous lesions of the jaws. Case presentation A 31-year-old female patient presented with a hard, non-fluctuating protrusion in the vestibule of the upper right maxilla. It was visualized on cone beam computed tomography (CBCT) as space-occupying osteolysis with the displacement of the floor and facial wall of the maxillary sinus, mimicking a cyst-like lesion. The tissue was surgically removed and identified as an OF in the histopathological examination. One year after the surgery, restitution of regular sinus anatomy and physiological intraoral findings were observed. Conclusions This case report emphasizes that rare entities, like the maxillary OF presented, often demonstrate nonspecific clinical and radiological findings. Nevertheless, clinicians need to consider rare entities as possible differential diagnoses and plan the treatment accordingly. Histopathological examination is essential to conclude the diagnosis. OF rarely recur after proper enucleation.